2023
DOI: 10.7759/cureus.41902
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Student-Led Musculoskeletal and Vascular Ultrasound Workshops at a Single Institution: A Retrospective Survey Analysis

Abstract: Introduction Point-of-care ultrasound (POCUS) is a rapidly evolving field of diagnostic medicine as its low cost, portability, and versatility have made handheld ultrasound (US) probes an invaluable tool for many modern physicians. Despite US’s benefits as a bedside evaluative tool, many medical schools have not integrated POCUS into their pre-clerkship medical education due to a lack of equipment and faculty. The first objective of our study was to determine whether student tutors (STs) would be ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This could be due to a number of factors, one of which could be that students perceive UI as seasoned experts in their field, which in turn bolsters the students' confidence in sonographic ability since they perceive to be learning from experts rather than their peers. However, other studies have shown that STs instill more confidence in medical students in the setting of ultrasound instruction [18][19][20][21]22,23]. One of these studies stated that their data and medical student evaluations suggested that this may be due to peer tutors' ability to conform their teachings to fit the learning style of other students [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to a number of factors, one of which could be that students perceive UI as seasoned experts in their field, which in turn bolsters the students' confidence in sonographic ability since they perceive to be learning from experts rather than their peers. However, other studies have shown that STs instill more confidence in medical students in the setting of ultrasound instruction [18][19][20][21]22,23]. One of these studies stated that their data and medical student evaluations suggested that this may be due to peer tutors' ability to conform their teachings to fit the learning style of other students [24].…”
Section: Discussionmentioning
confidence: 99%
“…This paper endeavors to investigate the efficacy of STs trained by other students in imparting the fundamentals of one of the most straightforward ultrasound uses: the musculoskeletal (MSK) ultrasound of the upper extremity. Other studies exploring the use of STs to educate on MSK ultrasound exist [15], in addition to other studies with emphasis on different body systems, including cardiac, vascular, and abdominal ultrasounds [16][17][18]. However, none explored the specific potential of a peer tutoring system that is completely independent of formal ultrasound instruction by faculty members and driven solely by student-taught tutors.…”
Section: Introductionmentioning
confidence: 99%